2015
DOI: 10.1007/s40725-015-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Forest Above-Ground Biomass Using Active and Passive Remote Sensing at Large (Subnational to Global) Scales

Abstract: Within the global forest area, a diverse range of forest types exist with each supporting varying amounts of biomass and allocations to different plant components. At country to continental scales, remote sensing techniques have been progressively developed to quantify the above-ground biomass (AGB) of these forests, with these based on optical, radar, and/or light detection and ranging (LiDAR) (airborne and spaceborne) data. However, none have been found to be globally applicable at high (≤30 m) resolution, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 80 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…It is anticipated that a major driver for large-scale plot acquisition campaigns using TLS will be the calibration and validation of these satellite-based sensors for large-area aboveground biomass mapping [82]. Existing plot inventory data will not be sufficient, since it has been shown that a major source of difference between pan-tropical biomass maps is the result of inadequate ground data and allometrics for spatial extrapolation of satellite measurements [83].…”
Section: Methods Developmentmentioning
confidence: 99%
“…It is anticipated that a major driver for large-scale plot acquisition campaigns using TLS will be the calibration and validation of these satellite-based sensors for large-area aboveground biomass mapping [82]. Existing plot inventory data will not be sufficient, since it has been shown that a major source of difference between pan-tropical biomass maps is the result of inadequate ground data and allometrics for spatial extrapolation of satellite measurements [83].…”
Section: Methods Developmentmentioning
confidence: 99%
“…Steininger [31], for example, found the canopy reflectance-biomass relationship to saturate at around 150 Mg/ha, while [37] reported that the above-ground biomass, below-ground biomass and necromass estimates for the large geographical expanse of the Brazilian Amazon could vary from minimum estimates of 78 billion Mg up to a maximum of 186 billion Mg. Another approach for estimating biomass by remote sensing is based on canopy density [38,39], as presented on tree cover percentage maps. The SAR-based technologies are rather sensitive to environmental conditions on a per scene basis [40] and have many challenges in worldwide mapping campaigns. Topographic reliefs, precise viewing angles and wet conditions are difficult to control in large area SAR data mosaic processing.…”
Section: State Of Forests -Biomass and Vegetation Structurementioning
confidence: 99%
“…TerraSAR) and processing techniques have increased the expectations towards a feasible SAR mapping concept [40]. Saatchi et al [44] have demonstrated the high sensitivity of P-and L-band airborne SAR observations to above-ground biomass (AGB) <300 Mg/ ha on a one-hectare scale.…”
Section: State Of Forests -Biomass and Vegetation Structurementioning
confidence: 99%
See 2 more Smart Citations